The effect of combined phacoemulsification and endo-cyclophotocoagulation on intraocular pressure fluctuation assessed by the water drinking test in patients with primary open angle glaucoma - Mohammad Razali, Amirah; Tang, Seng Fai; Syed Zakaria, Syed Zulkifli; Che-Hamzah, Jemaima; Aung, Tin; Othman, Othmaliza; Md Din, Norshamsiah (Karger Publishers, 2023)
Introduction: The aim of this study was to assess the effect of phacoemulsification and endo-cyclophotocoagulation (phaco-ECP) on intraocular pressure (IOP) fluctuation as assessed by the water drinking test (WDT) in primary open angle glaucoma (POAG). Methods: This was a prospective observational study carried out at a tertiary referral centre. POAG patients on topical antiglaucoma medications and planned for phaco-ECP were recruited. WDT was performed before surgery and 6 weeks postoperatively by drinking 10 mL/kg of water in 5 min followed by serial IOP by Goldmann applanation tonometry measurements at 15, 30, 45, and 60 min. Mean IOP, IOP fluctuation (difference between highest and lowest IOP), IOP reduction, and factors affecting IOP fluctuation were analysed. Results: Twenty eyes from 17 patients were included. Baseline IOP was similar before (14.7 ± 2.7 mm Hg) and after (14.8 ± 3.4 mm Hg, p = 0.90) surgery. There was no difference in mean IOP (17.6 ± 3.4 mm Hg vs. 19.3 ± 4.7 mm Hg pre- and postoperative, respectively, p = 0.26) or peak IOP (19.37 ± 3.74 mm Hg vs. 21.23 ± 5.29 mm Hg, p = 0.25), albeit a significant reduction in IOP-lowering medications (2.2 ± 1.15 vs. 0.35 ± 0.93, p < 0.001) postoperatively. IOP fluctuation was significantly greater (6.4 ± 3.2 mm Hg vs. 4.6 ± 2.1 mm Hg, p = 0.015) with more eyes having significant IOP fluctuation of ≥6 mm Hg (11 eyes [55%] vs. 4 eyes [20%], p < 0.001) postoperatively. Factors that were significantly associated with increased postoperative IOP fluctuations were higher preoperative IOP fluctuation (β = 0.69, 95% CI 0.379–1.582, p = 0.004) and more number of postoperative antiglaucoma medications (β = 0.627, 95% CI 0.614–3.322, p = 0.008). Conclusion: Reducing aqueous production with phaco-ECP does not eliminate IOP fluctuation in POAG patients. The increase in postoperative IOP fluctuation suggests increased outflow resistance after phaco-ECP.